Efforts to Promote Occupational Safety and Health for the Implementation of the Covid-19 Control Health Protocol in Manufacturing Companies - Fitri Sari Dewi (Jurnal EduHealth, 2023)
Entering the new normal era, companies are starting to reorganize work patterns. This is related to the ongoing outbreak of Covid-19 followed by an increase in working conditions, so that companies are required to comply with the Covid-19 health protocol. As stated in circular letter Number HK.02.01/MENKES/335/2020 concerning Protocols for Prevention of Transmission of Corona Virus Disease (Covid-19) in Workplaces in the Service and Trade Sector. Health promotion is an important determinant in efforts to change people's behavior, especially workers who continue to work during the Covid-19 pandemic. The purpose of this study is to ana lyze efforts to promote occupational safety and health (K3) towards the implementation of the Covid-19 control health protocol. This research is an observational study with a cross sectional study design. The population in this study were all company employees. The sample in this study is the total population of 64 employees. The results of this study indicate that there are efforts to promote OSH, namely 30 (46.9%) respondents considered it sufficient and as many as 46 (71.9%) respondents considered that the implementation of the health protocol for controlling Covid-19 was good. It was concluded that there was a relationship between OSH promotion and the implementation of the Covid-19 control health protocol with a P va lue of 0.000 <0.05. It is recommended that companies increase supervision of workers to comply with health protocols when working.